BALA PALA INDONESIA: CREATIVE PROCESS OF CONCEPTUAL ILLUSTRATION BASED ART FASHION - Mudarahayu, Tiartini (International Journal of Social Science, 2025)
Banda nutmeg sparked conflict, until thenegotiations culminated in the signing of three peace treaties known as the Treaty of Breda, one of which concerned the exchange of Run Island and Manhattan. Seeing Banda nutmegas a subject that can be read as a source of inspiration with an interdisciplinary basis for art fashion, the author chose illustrations with the phenomenon of `Cinderella` art as the background, as a medium for expressing the work. The method used is the elaboration of frangipani and three aesthetic approaches by referring to the theoretical foundations of creativity, product semantics, and phenomenological aesthetics. The results of the research synthesis of creation in the form of novelty conceptual illustration works based on art fashion in the collection of works "Bala Pala Indonesia", seven works in textile media with interdisciplinary creative processing techniques. The formulation of the stages of the creative process in question consists of: 1) Determination of the subject of creation; 2) Research consisting of a review of literature and sources of works with similar ideas that have existed previously and experimental research on the subject of creation as well as; 3) Exploration of forms, mediums, and creative techniques based on research results; 4) sample creation; 5) embodiment of the work; 6) presentation of the work. These process stages are flexible and can be adjusted to the needs of users.